Functional characterization and expression of GASCL1 and GASCL2, two anther-specific chalcone synthase like enzymes from Gerbera hybrida. (February 2017) - Kontturi, Juha; Osama, Raisa; Deng, Xianbao; Bashandy, Hany; Albert, Victor A.; Teeri, Teemu H.
Abstract: The chalcone synthase superfamily consists of type III polyketidesynthases (PKSs), enzymes responsible for producing plant secondary metabolites with various biological and pharmacological activities. Anther-specific chalcone synthase-like enzymes (ASCLs) represent an ancient group of type III PKSs involved in the biosynthesis of sporopollenin, the main component of the exine layer of moss spores and mature pollen grains of seed plants. In the latter, ASCL proteins are localized in the tapetal cells of the anther where they participate in sporopollenin biosynthesis and exine formation within the locule. It is thought that the enzymes responsible for sporopollenin biosynthesis are highly conserved, and thus far, each angiosperm species with a genome sequenced has possessed two ASCL genes, which in Arabidopsis thaliana are PKSA and PKSB. The Gerbera hybrida (gerbera) PKS protein family consists of three chalcone synthases (GCHS1, GCHS3 and GCHS4) and three 2-pyrone synthases (G2PS1, G2PS2 and G2PS3). In previous studies we have demonstrated the functions of chalcone synthases in flavonoid biosynthesis, and the involvement of 2-pyrone synthases in the biosynthesis of antimicrobial compounds found in gerbera. In this study we expanded the gerbera PKS-family by functionally characterizing two gerbera ASCL proteins. In vitro enzymatic studies using purified recombinant proteins showed that both GASCL1 and GASCL2 were able to use medium and long-chain acyl-CoA starters and perform two to three condensation reactions of malonyl-CoA to produce tri- and tetraketide 2-pyrones, usually referred to as alpha-pyrones in sporopollenin literature. Both GASCL1 and GASCL2 genes were expressed only in floral organs, with most expression observed in anthers. In the anthers, transcripts of both genes showed strict tapetum-specific localization. Graphical abstract: Gerbera tapetum localized GASCL1 and GASCL2 are tri-and tetraketide synthases capable of using long chain acyl-CoA starters. Highlights: Two anther-specific chalcone synthases (ASCLs) from Gerbera hybrida were characterized. GASCL1 and GASCL2 are tri-and tetraketidesynthases that utilize long chain acyl-CoA starters. GASCL1 and GASCL2 have tapetum localized expression. This study extends the type III polyketide synthase family from Gerbera hybrida to two members that are very distinct from chalcone synthase.